Optimization of an ex vivo wound healing model in the adult human skin: Functional evaluation using photodynamic therapy. Issue 5 (8th September 2015) - Mendoza‐Garcia, Jenifer; Sebastian, Anil; Alonso‐Rasgado, Teresa; Bayat, Ardeshir
ABSTRACT Limited utility of in vitro tests and animal models of human repair, create a demand for alternative models of cutaneous healing capable of functional testing. The adult human skin Wound Healing Organ Culture (WHOC) provides a useful model, to study repair and enable evaluation of therapies such as the photodynamic therapy (PDT). Thus, the aim here was to identify the optimal WHOC model and to evaluate the role of PDT in repair. Wound geometry, system of support, and growth media, cellular and matrix biomarkers were investigated in WHOC models. Subsequently, cellular activity, extracellular matrix remodeling, and oxidative stress plus gene and protein levels of makers of wound repair measured the effect of PDT on the optimized WHOC. WHOCs embedded in collagen and supplemented DMEM were better organized showing stratified epidermis and compact dermis with developing neo‐epidermis. Post‐PDT, the advancing reepithelialization tongue was 3.5 folds longer, and was highly proliferative with CK‐14 plus p16 increased (p < 0.05) compared to controls. The neo‐epidermis was fully differentiated forming neo‐collagen. Proliferating nuclear antigen, p16, COLI, COLIII, MMP3, MMP19, and α‐SMA were significantly more expressed (p < 0.05) in dermis surrounding the healing wound. In conclusion, an optimal model of WHOC treated with PDT shows increased reepithelialization and extracellular matrix reconstruction and remodeling, supporting evidence toward development of an optimal ex vivo wound healing model.